Multimodal roles of transient receptor potential channel activation in inducing pathological tissue scarification - Zheng, Yuping; Huang, Qingrui; Zhang, Yanfeng; Geng, Lanxin; Wang, Wuqing; Zhang, Huimin; He, Xiang; Li, Qiannan (Frontiers in Immunology, 2023)
Transient receptor potential (TRP) channels are a class of transmembrane proteins that can sense a variety of physical/chemical stimuli, participate in the pathological processes of various diseases and have attracted increasing attention from researchers. Recent studies have shown that some TRP channels are involved in the development of pathological scarification (PS) and directly participate in PS fibrosis and re-epithelialization or indirectly activate immune cells to release cytokines and neuropeptides, which is subdivided into immune inflammation, fibrosis, pruritus and mechanical forces increased. This review elaborates on the characteristics of TRP channels, the mechanism of PS and how TRP channels mediate the development of PS, summarizes the important role of TRP channels in the different pathogenesis of PS and proposes that therapeutic strategies targeting TRP will be important for the prevention and treatment of PS. TRP channels are expected to become new targets for PS, which will make further breakthroughs and provide potential pharmacological targets and directions for the in-depth study of PS.